(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
Severe obesity represents a major challenge in modern surgery, influencing not only the incidence of abdominal wall defects but also the outcomes and safety of their surgical repair. Ventral hernias, including incisional and primary abdominal wall hernias, are significantly more prevalent among individuals with severe obesity compared to the general population. Increased intra-abdominal pressure, altered connective tissue metabolism, impaired wound healing, and chronic low-grade inflammation collectively contribute to both hernia formation and recurrence in this patient group. As the global prevalence of obesity continues to rise, the burden of ventral hernias in obese patients has become an increasingly important clinical problem.